Magnetically separable carbon-supported ruthenium cluster catalyst as well as preparation method and application thereof

By using a magnetically separable carbon-laminated ruthenium cluster catalyst, using a combination of nickel-coated graphene composite material and ruthenium clusters, the problems of low atom utilization and high cost of traditional catalysts are solved, efficient catalyzing of toluene hydrogenation at low temperatures, and an environmentally friendly and economical hydrogen storage system is realized through magnetic recovery.

CN119702004APending Publication Date: 2025-03-28INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411889397.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional toluene hydrogenation catalysts have problems with low atomic utilization and high metal cost, and it is difficult to achieve a hydrogen storage system with high activity and high stability at low temperatures.

Method used

A magnetically separable carbon-supported ruthenium cluster catalyst is used. The catalyst is coated with nickel-coated graphene composite material as a carbon support. The ruthenium is distributed on the surface of the graphene shell layer in clusters, and the catalyst is separated and recovered through an external magnetic field.

Benefits of technology

Under mild conditions (80-110℃, 10-30bar hydrogen pressure), the hydrogenation of toluene is efficiently catalyzed to form methylcyclohexane, achieving a toluene conversion rate of 100%, and a methylcyclohexane yield of 99.9%. It saves costs through magnetic recovery, and has high atomic economy and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702004A_ABST
    Figure CN119702004A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of toluene hydrogenation catalysts, and particularly relates to a magnetically separable carbon-supported ruthenium cluster catalyst as well as a preparation method and application thereof. According to the catalyst, a nickel-coated graphene core-shell structure carbon material is used as a carrier, and ruthenium is loaded on a graphene shell layer in a cluster form through a deposition and precipitation method. The catalyst can efficiently catalyze toluene hydrogenation to generate methylcyclohexane under the mild condition of 80-110 DEG C and the hydrogen pressure of 10-30 bar. Compared with a traditional catalyst, the magnetic separable catalyst not only can work under a relatively mild condition, but also can be separated, recycled and reused by externally applying a magnetic field, so that the targets of environmental protection, energy conservation and emission reduction are further achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of toluene hydrogenation catalysts, and specifically relates to a magnetically separable carbon-supported ruthenium cluster catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen has received widespread attention as a carbon-neutral energy source, but the development of efficient and safe hydrogen storage technology remains a huge challenge. In recent years, liquid organic hydrogen carrier (LOHC) technology has shown great potential in efficient and stable hydrogen storage and transportation. This technology can achieve safe and economical large-scale transoceanic transportation and long-term hydrogen storage. Among the many LOHC systems, the toluene hydrogenation reaction pathway is simple and does not have too many intermediates. Methylcyclohexane has a hydrogen storage capacity of 6.2wt.%, is liquid at room temperature, and is a good hydrogen storage system.

[0003] Compared with homogeneous catalysts, heterogeneous catalysts have better separation and recovery performance and show wider application prospects. Traditional toluene hydrogenation catalysts are usually precious metal particle catalysts, which have problems of low atomic utilization and high metal cost. Atomically dispersed fully exposed cluster catalysts not only retain metal active sites, but also significantly improve atomic utilization. They show good development potential in the field of toluene hydrogenation and are expected to develop LOHC toluene hydrogenation catalysts with high activity and high stability at low temperatures. Summary of the invention

[0004] The purpose of the present invention is to provide a magnetically separable carbon-supported ruthenium cluster catalyst and its preparation method and application. The prepared magnetically separable ruthenium cluster catalyst is applied to toluene hydrogenation to produce methylcyclohexane, so as to achieve efficient toluene hydrogenation under relatively mild conditions, and the catalyst can be separated and recovered by applying an external magnetic field.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A magnetically separable carbon-supported ruthenium cluster catalyst uses ruthenium as an active ingredient and a nickel-coated graphene composite material as a carbon carrier. Ruthenium is distributed in the form of clusters on the surface of the nickel-coated graphene composite material.

[0007] Furthermore, the nickel-coated graphene composite carbon carrier is a core-shell structure, wherein the core is nickel and the outer shell is graphene; ruthenium is distributed in clusters on the surface of the graphene outer shell and forms bonds with carbon atoms at defects in the graphene.

[0008] Furthermore, the nickel contained in the carbon carrier imparts magnetic properties to the carrier.

[0009] Furthermore, the ruthenium loading in the catalyst is 0.3-1.0wt%, preferably 0.5-1.0wt%; the particle size of the ruthenium cluster is 1-2nm; the particle size of the nickel in the carbon carrier is 5-7nm; and the thickness of the graphene shell is 1-2nm.

[0010] Furthermore, a method for preparing a magnetically separable carbon-supported ruthenium cluster catalyst comprises the following steps:

[0011] (1) taking nickel hydroxide and citric acid monohydrate to react in water; drying the obtained nickel citrate aqueous solution to obtain a nickel citrate complex, and after high-temperature pyrolysis treatment, pickling with concentrated hydrochloric acid, washing, and drying, thereby obtaining a magnetic nickel-coated graphene composite carbon carrier;

[0012] (2) Preparation of magnetically separable carbon-supported ruthenium cluster catalyst precursor by sedimentation precipitation method: Take the magnetic nickel-coated graphene composite carbon carrier obtained in step (1) and dissolve it in water. Under stirring conditions, add a precipitant to adjust the pH to 10-11. Calculate the amount of ruthenium chloride solution according to the ruthenium loading amount, add it to the above aqueous solution, stir the reaction, separate the solid and liquid, and dry it to obtain a magnetically separable carbon-supported ruthenium cluster catalyst precursor;

[0013] (3) Reducing the magnetically separable carbon-supported ruthenium cluster catalyst precursor: reducing the magnetically separable carbon-supported ruthenium cluster catalyst precursor in a hydrogen atmosphere, and cooling the temperature to room temperature in an inert atmosphere after reduction to obtain a magnetically separable carbon-supported ruthenium cluster catalyst.

[0014] Furthermore, the molar ratio of nickel hydroxide to citric acid monohydrate described in step (1) is 1:1-10, preferably 1:2-6; the concentration of nickel hydroxide in water is 0.72 mol / L, the reaction temperature is 50-100°C, preferably 60-90°C; the reaction time is 4-10h, preferably 5-8h; the high-temperature pyrolysis treatment process is: placing the nickel citrate complex in a high-temperature pyrolysis device, the temperature is 500-900°C, the heating rate is 0.5-15°C / min, preferably 2-10°C / min, the gas condition is an inert atmosphere of 30-80ml / min, and the inert atmosphere is Ar, He or N 2 One or more of the above, the reaction time is 1 to 6 hours; the concentration of the concentrated hydrochloric acid is 8 to 10 mol / L, the pickling time is 8 to 20 hours, and the temperature is 20 to 60°C; the washing is performed by washing with deionized water and anhydrous ethanol in sequence.

[0015] Furthermore, the mass of the carrier described in step (2) is 150-250 mg, preferably 180-220 mg; the volume of the water is 20-50 ml; the stirring temperature is 80-150° C.; the precipitant is one or more of sodium formate, sodium carbonate and sodium bicarbonate; the mass concentration of ruthenium in the ruthenium chloride solution is 0.2-1.0 mg / mL, preferably 0.3-0.5 mg / mL; and the reaction time is 1-3 h.

[0016] Furthermore, in step (3), the hydrogen atmosphere is a mixture of hydrogen and an inert gas with a hydrogen volume content of 100% or a hydrogen volume content of 50% to 100%, and the inert gas is Ar, He or N 2 One or more of the following; the reduction temperature is 100-300°C, and the reduction time is 1-2h; the inert atmosphere is Ar, He or N 2 One or more of the above, the gas flow rate is 10-30 ml / min.

[0017] The invention discloses an application of a magnetically separable carbon-supported ruthenium cluster catalyst as a catalyst in the hydrogenation of toluene to prepare methylcyclohexane.

[0018] Furthermore, in the toluene hydrogenation reaction process, the reactant is toluene, the solvent is one of dodecane, cyclohexane, n-hexane and decahydronaphthalene, the hydrogen source is hydrogen, the ratio of the catalyst to toluene is (20-50) mg:0.5 mmol, the ratio of toluene to solvent is (0.2-1) mmol:10 ml, the reaction temperature is 80-110° C.; the hydrogen pressure is 10-30 bar; and the reaction time is 0.5-3 h.

[0019] The advantages of the present invention are as follows:

[0020] 1. The carrier material of the catalyst of the present invention is a nickel-coated graphene composite material, which is rich in defects and oxygen-containing functional groups on the surface, which helps to stably attach ruthenium atoms to the surface through strong metal-carrier interactions. The active ingredient in the catalyst is ruthenium, which is loaded on the surface of the carrier in the form of clusters, thereby greatly improving the atomic utilization of ruthenium. In addition, the nickel particle core gives the carrier magnetism, which is convenient for separation from the reaction solution with the help of an external magnetic field, so as to achieve the recovery and reuse of the catalyst.

[0021] 2. When the catalyst of the present invention is used, toluene can be efficiently catalyzed to generate methylcyclohexane by hydrogenation at a temperature of 80 to 110°C and a hydrogen pressure of 10 to 30 bar, and a toluene conversion rate of 100% and a methylcyclohexane yield of 99.9% can be achieved. Compared with traditional catalysts, this magnetically separable catalyst can not only work under relatively mild conditions, but also realize the separation, recovery and reuse of the catalyst by applying an external magnetic field, further achieving the goals of green environmental protection, energy saving and emission reduction.

[0022] 3. The magnetically separable carbon-supported ruthenium cluster catalyst described in the present invention has a large number of atomically dispersed ruthenium nanoclusters on its surface, which greatly improves the atomic utilization of the metal, saves costs in industrial production and preparation, and has high atomic economy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a HAADF-STEM image of the carbon support of the catalyst of the present invention;

[0024] Figure 2 is a HAADF-STEM image of the catalyst of the present invention;

[0025] Figure 3 It is a state diagram of the catalyst during the reaction process of the present invention;

[0026] Figure 4 It is the catalytic stability result of the catalyst of the present invention. DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0028] Example 1

[0029] The preparation process of the catalyst in this embodiment is as follows:

[0030] The specific process of preparing the precursor solution using nickel hydroxide and citric acid monohydrate is as follows: nickel hydroxide and citric acid monohydrate are added to a flask at a molar ratio of 1:2, and 30 mL of deionized water is added. The concentration of nickel hydroxide in water is 0.72 mol / L. Stir in an oil bath at 80°C for 6 hours until it dissolves to form a uniform, clear and transparent nickel citrate solution. After the prepared precursor solution is dried in a blast drying oven, the obtained nickel citrate complex is placed in a quartz boat, and the quartz boat is placed in a tube furnace. It is pyrolyzed at 800°C in an Ar inert atmosphere for carbonization treatment. The heating rate is 5°C / min, the gas flow rate is 50 mL / min, and the treatment time is 2 hours. A magnetic nickel-coated graphene composite material is prepared, which is recorded as Ni@G-1. The composite material was then pickled with 60 mL of 10 mol / L concentrated hydrochloric acid at 40°C for 12 hours, and then thoroughly washed with 1 L of deionized water and 300 mL of anhydrous ethanol, and then placed in a vacuum drying oven at 60°C for 12 hours to obtain a magnetic nickel-coated graphene composite carbon carrier, denoted as Ni@G-2. The scanning transmission electron microscope photo of the composite material is shown in FIG. Figure 1As shown in the figure, a clear core-shell structure can be seen. The nickel core is coated with a graphene shell obtained by high-temperature pyrolysis of citric acid. The average particle size of nickel in the carbon carrier is 6.15nm (particle size distribution is 6-6.3nm); the average thickness of the graphene shell is 1nm (thickness range is 0.8-1.2nm), with a clear core-shell structure.

[0031] Take 200 mg of the magnetic carbon carrier and add it into a 100 ml round-bottom flask, add 30 ml of deionized water, heat the oil bath to 100 °C, add Na 2 CO 3 precipitant, and adjust the pH to 11. Calculate the amount of ruthenium chloride based on the target ruthenium loading, starting from RuCl with a Ru content of 100 mg / mL 3 180 μL of the solution was drawn and prepared into a precursor solution with a Ru concentration of 0.4 mg / mL, which was added dropwise to the above flask and stirred for 1 hour. After standing to room temperature, it was filtered and placed in a vacuum drying oven at 60°C for 12 hours to obtain a magnetic carbon-supported ruthenium cluster catalyst precursor. Then, the catalyst precursor was reduced in a hydrogen atmosphere at 200°C for 1 hour. After treatment, it was cooled to room temperature in an argon atmosphere of 10 to 30 ml / min (here 20 ml / min) to obtain a magnetically separable carbon-supported ruthenium cluster catalyst. The mass of ruthenium accounted for 0.8wt.% of the carbon carrier of the nickel-coated graphene composite material. It is recorded as 0.8Ru / Ni@G-2, and its scanning transmission electron microscope photo is shown in Figure 2 As shown, it can be seen that Ru clusters with a size of 1 to 2 nm are evenly distributed on the surface of the carrier.

[0032] Example 2

[0033] This example is a test of the catalytic performance of toluene hydrogenation of the catalyst prepared in Example 1:

[0034] The catalyst performance test was carried out using a stainless steel high-pressure reactor. 30 mg 0.8Ru / Ni@G-2 was added to the 50 ml quartz liner of the reactor, and 10 ml dodecane solution containing 0.5 mmol toluene was added. The liner was placed in the stainless steel reactor and sealed. The air was replaced with argon seven times, and the argon was replaced with hydrogen six times. Then the temperature was raised to 110 °C, and H 2 The reaction was stirred at a pressure of 2.5 MPa, a stirring rate of 800 r / min, and a reaction time of 60 min. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 51.3%, and the yield of methylcyclohexane was 50.4%.

[0035] Example 3

[0036] The operation of Example 2 was followed, with other conditions remaining unchanged, except that the reaction time was 120 min. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 86.7%, and the yield of methylcyclohexane was 86.5%.

[0037] Example 4

[0038] The operation of Example 2 was followed, with other conditions remaining unchanged, except that the amount of catalyst was 40 mg and the reaction time was 120 min. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 100%, and the yield of methylcyclohexane was 99.9%.

[0039] Example 5

[0040] The operation of Example 2 was followed, and other conditions remained unchanged, except that the reaction temperature was 100°C and the reaction time was 120 min. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 72.4%, and the yield of methylcyclohexane was 72.4%.

[0041] Example 6

[0042] The operation of Example 2 was followed, with other conditions remaining unchanged, except that the reaction pressure was 2 MPa and the reaction time was 120 min. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 81.3%, and the yield of methylcyclohexane was 81.2%.

[0043] Example 7

[0044] The operation of Example 4 was followed, and other conditions remained unchanged. The only catalyst used was the recycled catalyst, and the catalyst cycle stability test was performed. After each reaction, the catalyst was left to stand and wait for the magnetic particles to adsorb the catalyst. Figure 3 They are the states of the catalyst before, during and after the reaction, respectively. Before the reaction, a small amount of catalyst will be adsorbed on the magnet. During the reaction, the reaction speed is set to 800r / min. Due to the effect of centrifugal force, the catalyst will be completely separated from the magnet and participate in the catalytic reaction. After the reaction, let it stand and wait for the magnet to adsorb all the catalysts in the reaction system. Then use a magnet to adsorb the magnet and catalyst on the outer wall of the container, pour out the supernatant, and then wash with a large amount of water and anhydrous ethanol. After standing again, use a magnet to adsorb the magnet and catalyst on the outer wall of the container again, and pour out the supernatant. The above washing-adsorption-pouring out of the supernatant process is repeated three times, and then the recovered catalyst is placed in a 60°C vacuum drying oven and dried for 6 hours. Then, the cyclic reaction test is carried out according to the steps of Example 4, and this is repeated five times. After each reaction, the composition of the reaction product is analyzed by gas chromatography to obtain the stability test data of the catalyst, such as Figure 4 shown.

[0045] Comparative Example 1

[0046] The catalyst was prepared according to the method of Example 1, except that the noble metal ruthenium cluster was not loaded, that is, the pure carrier was used for toluene hydrogenation, and was recorded as Ni@G-2. The operation of Example 4 was followed, the reaction time was 120 min, and other conditions remained unchanged. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 0.

[0047] Comparative Example 2

[0048] The catalyst was prepared according to the method of Example 1, except that a magnetic nickel-graphene composite material obtained by high-temperature pyrolysis was used as the catalyst, and no acid washing and precious metal ruthenium loading were performed, which was recorded as Ni@G-1. The operation of Example 4 was followed, and other conditions remained unchanged. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 0.

[0049] Comparative Example 3

[0050] The catalyst was prepared according to the method of Example 1, except that the precious metal ruthenium was directly loaded on the magnetic nickel-graphene composite material obtained by high-temperature pyrolysis without acid washing, and the loading amount of ruthenium was still 0.8wt.%. The operation of Example 4 was followed, and other conditions remained unchanged. The prepared catalyst was recorded as 0.8Ru / Ni@G-1. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 0.

[0051] Comparative Example 4

[0052] The catalyst was prepared according to the method of Example 1, except that the loading amount of the precious metal ruthenium was adjusted to 0.3wt%, denoted as 0.3Ru / Ni@G-2, wherein the ruthenium was distributed on the surface of the nickel-coated graphene material in the form of a single atom. The operation of Example 4 was followed, and other conditions remained unchanged. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 5.2%.

[0053] Comparative Example 5

[0054] The catalyst was prepared according to the method of Example 1, except that the loading amount of the precious metal ruthenium was adjusted to 1.0wt%, denoted as 1.0Ru / Ni@G-2, wherein the ruthenium was distributed on the surface of the nickel-coated graphene material in the form of particles. The operation of Example 4 was followed, and other conditions remained unchanged. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 26.9%.

[0055] Comparative Example 6

[0056] The catalyst was prepared according to the method of Example 1, except that the carrier was adjusted to SiO 2 , the ruthenium loading is still 0.8wt.%, recorded as 0.8Ru / SiO2 The operation of Example 4 was followed, with other conditions remaining unchanged. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 7.6%.

[0057] Comparative Example 7

[0058] The catalyst was prepared according to the method of Example 1 except that the carrier was adjusted to Al 2 O 3 , the ruthenium loading is still 0.8wt.%, recorded as 0.8Ru / Al 2 O 3 The operation of Example 4 was followed, with other conditions remaining unchanged. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 14.7%.

[0059] Comparative Example 8

[0060] The catalyst was prepared according to the method of Example 1, except that the carrier was adjusted to defect-rich nanodiamond (ND@G), and the ruthenium loading was still 0.8wt.%, recorded as 0.8Ru / ND@G. The operation was carried out according to Example 4, and other conditions remained unchanged. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and the toluene conversion rate was 1.3%.

[0061] Based on the above experimental results, it can be understood that the new magnetically separable ruthenium cluster catalyst proposed in the present invention not only has good hydrogenation performance, but also can be separated, recovered and reused through an external magnetic field and the magnetic properties of the carrier itself, which saves production costs and is more environmentally friendly.

[0062] The above embodiments are for reference only. Technical solutions similar to the present invention or extended from the concept of this patent are all within the protection scope of the present invention.

Claims

1. A magnetically separable carbon-supported ruthenium cluster catalyst, characterized in that: Ruthenium is used as an active ingredient, a nickel-coated graphene composite material is used as a carbon carrier, and ruthenium is distributed on the surface of the nickel-coated graphene composite material.

2. The magnetically separable carbon-supported ruthenium cluster catalyst according to claim 1, characterized in that: The nickel-coated graphene composite carbon carrier is a core-shell structure, wherein the core is nickel and the outer shell is graphene; ruthenium is distributed on the surface of the graphene outer shell in the form of clusters and forms bonds with carbon atoms at defects in the graphene.

3. The magnetically separable carbon-supported ruthenium cluster catalyst according to claim 1, characterized in that: The nickel contained in the carbon carrier imparts magnetic properties to the carrier.

4. The magnetically separable carbon-supported ruthenium cluster catalyst according to any one of claims 1 to 3, characterized in that: The ruthenium loading in the catalyst is 0.3-1.0wt%, preferably 0.5-1.0wt%; the particle size of the ruthenium cluster is 1-2nm; the particle size of the nickel in the carbon carrier is 5-7nm; and the thickness of the graphene shell is 1-2nm.

5. A method for preparing a magnetically separable carbon-supported ruthenium cluster catalyst according to any one of claims 1 to 3, characterized in that: The steps include: (1) taking nickel hydroxide and citric acid monohydrate to react in water; drying the obtained nickel citrate aqueous solution to obtain a nickel citrate complex, and after high-temperature pyrolysis treatment, pickling with concentrated hydrochloric acid, washing, and drying, thereby obtaining a magnetic nickel-coated graphene composite carbon carrier; (2) Preparation of magnetically separable carbon-supported ruthenium cluster catalyst precursor by sedimentation precipitation method: Take the magnetic nickel-coated graphene composite carbon carrier obtained in step (1) and dissolve it in water. Under stirring conditions, add a precipitant to adjust the pH to 10-11. Calculate the amount of ruthenium chloride solution according to the ruthenium loading amount, add it to the above aqueous solution, stir the reaction, separate the solid and liquid, and dry it to obtain a magnetically separable carbon-supported ruthenium cluster catalyst precursor; (3) Reducing the magnetically separable carbon-supported ruthenium cluster catalyst precursor: reducing the magnetically separable carbon-supported ruthenium cluster catalyst precursor in a hydrogen atmosphere, and cooling the temperature to room temperature in an inert atmosphere after reduction to obtain a magnetically separable carbon-supported ruthenium cluster catalyst.

6. The method for preparing the magnetically separable carbon-supported ruthenium cluster catalyst according to claim 5, characterized in that: The molar ratio of nickel hydroxide to citric acid monohydrate described in step (1) is 1:1-10, preferably 1:2-6; the concentration of nickel hydroxide in water is 0.72 mol / L, the reaction temperature is 50-100°C, preferably 60-90°C; the reaction time is 4-10h, preferably 5-8h; the high-temperature pyrolysis treatment process is: placing the nickel citrate complex in a high-temperature pyrolysis device, the temperature is 500-900°C, the heating rate is 0.5-15°C / min, preferably 2-10°C / min, the gas condition is an inert atmosphere of 30-80ml / min, the inert atmosphere is one or more of Ar, He or N2, and the reaction time is 1-6h; the concentrated hydrochloric acid concentration is 8-10 mol / L, the pickling time is 8-20h, and the temperature is 20-60°C; the washing is washing with deionized water and anhydrous ethanol in sequence.

7. The method for preparing a magnetically separable carbon-supported ruthenium cluster catalyst according to claim 5, characterized in that: The mass of the carrier described in step (2) is 150-250 mg, preferably 180-220 mg; the volume of the water is 20-50 ml; the stirring temperature is 80-150° C.; the precipitant is one or more of sodium formate, sodium carbonate and sodium bicarbonate; the mass concentration of ruthenium in the ruthenium chloride solution is 0.2-1.0 mg / mL, preferably 0.3-0.5 mg / mL; and the reaction time is 1-3 h.

8. The method for preparing a magnetically separable carbon-supported ruthenium cluster catalyst according to claim 5, characterized in that: In step (3), the hydrogen atmosphere is a mixed gas of hydrogen with a hydrogen volume content of 100% or a hydrogen volume content of 50% to 100% and an inert gas, and the inert gas is one or more of Ar, He or N2; the reduction temperature is 100 to 300°C, and the reduction time is 1 to 2h; the inert atmosphere is one or more of Ar, He or N2, and the gas flow rate is 10 to 30ml / min.

9. Use of the magnetically separable carbon-supported ruthenium cluster catalyst according to any one of claims 1 to 3 as a catalyst in the hydrogenation of toluene to produce methylcyclohexane.

10. The use according to claim 9, characterized in that: In the toluene hydrogenation reaction process, the reactant is toluene, the solvent is one or more of dodecane, cyclohexane, n-hexane and decahydronaphthalene, the hydrogen source is hydrogen, the ratio of the catalyst to toluene is (20-50) mg:0.5 mmol, the ratio of toluene to solvent is (0.2-1) mmol:10 ml, the reaction temperature is 80-110° C., the hydrogen pressure is 10-30 bar, and the reaction time is 0.5-3 h.

Citation Information

Cited By

  • Preparation method and application of Pd NPs-ZrO2 / C composite material derived from MOFs

    CN121490753A

  • Magnetic field separable catalyst for partial hydrogenation of benzene to prepare cyclohexene and preparation method thereof

    CN122230745A